Pengaruh Penggunaan Media Sosial Sebagai Alat Komunikasi Individu Terhadap Loyalitas Lingkungan Sekitar Polrestabes RT 18 Jakabaring - Wijaya, Aldi; Wibisana, Satrio; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to determine the influence of the use of social media as a tool for individual communication on environmental loyalty around Polrestabes RT 18 Jakabaring, Palembang. The method used is a quantitative approach through the distribution of questionnaires to 30 respondents and analyzed with the help of SPSS. The results of the bar graph indicate that the majority of respondents (86.7%) agree that social media plays a role in increasing environmental awareness. Simple linear regression analysis produces an equation Y = 11.060 + 0.714X with an R² value of 0.341, indicating a positive and significant relationship between the two variables. These findings suggest that the use of social media can be an effective means to encourage community loyalty to the surrounding environment.